Steamboat along Snake River at Nome showing sand spit on the left and tents and buildings to the right, probably between 1899 and 1900 - Warner, Arthur Churchill, 1864-1943 (1899)
Gold was discovered on the Nome beaches in the Summer of 1899. By Spring of 1900, thousands had arrived for the gold rush. Warner 122 Filed in Alaska series.